Mechanism of Endoplasmic Reticulum Stress Pathway in the Osteogenic Phenotypic Transformation of Aortic Valve Interstitial Cells - Tao, Yiming; Geng, Yimin; Dang, Wenpei; Xu, Xinxin; Zhao, Hui; Zou, Lijuan; Li, Yongsheng (Frontiers in Endocrinology, 2022)
Background and Purpose Calcific Aortic Valve Disease (CAVD) is a crucial component of degenerative valvular disease in old age and with the increasing prevalence of the aging population. we hope that by modeling valvular osteogenesis and intervening with endoplasmic reticulum stress inhibitor TUDCA to observe the effect of endoplasmic reticulum stress on valve osteogenesis Methods In this study, rabbit heart valvular interstitial cells (VICs) were isolated and cultured. They treated with ox-LDL (Oxidized Low Density Lipoprotein) stimulation to establish a model of valvular osteogenic transformation. BMP2（Bone Morphogenetic Protein 2）, PERK（Protein kinase R-like endoplasmic reticulum kinase）, CHOP（CCAAT/enhancer-binding protein homologous protein） and transcriptional regulatory factor ATF4（Activating Transcription Factor 4 ）were recorded after intervention with ER stress inhibitor TUDCA. The effects of er stress on valvular osteogenic transformation were analyzed. Result After stimulation of VICs with ox-LDL, the expression levels of BMP2, PERK, CHOP, and ATF4 increased. However, TUDCA treatment can alleviate the increased expression levels of BMP2, PERK ATF4, and CHOP under ox-LDL stimulation to a certain extent. Conclusion The endoplasmic reticulum stress signaling pathway is involved in ox-LDL-induced calcification of rabbit valve interstitial cells. Inhibition of endoplasmic reticulum stress using TUDCA can improve the progression of rabbit aortic valve calcification.